Responsivitas Pemerintah Daerah terhadap Implementasi SDGs: Studi Empiris di Kabupaten Lombok Barat - Pranata, Ahmad Fauzan; Aisyah Rahmadani, Nur (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2024)
The implementation of the Sustainable Development Goals (SDGs) at the regional level demands government responsiveness in designing policies, programs, and public services that align with the principles of sustainable development. This study aims to analyze the responsiveness of the West Lombok Regency Government to SDG implementation, particularly in the planning, implementation, and evaluation of development policies. This research used an empirical approach with descriptive qualitative methods. Data were collected through in-depth interviews with relevant stakeholders, field observations, and analysis of regional planning documents. The results indicate that the West Lombok Regency Government has demonstrated a fairly good level of responsiveness in integrating SDG objectives into regional development planning documents. However, several obstacles remain, such as limited coordination between regional government agencies, suboptimal data utilization, and low public participation in the policy formulation process. Furthermore, consistent implementation of SDG programs remains challenging due to limited resources and institutional capacity. This study concludes that increasing local government responsiveness requires strengthened governance, cross-sectoral collaboration, and the development of sustainable monitoring and evaluation mechanisms to support optimal SDG achievement at the local level.